1983
DOI: 10.1099/0022-1317-64-12-2717
|View full text |Cite
|
Sign up to set email alerts
|

Variable Restriction Endonuclease Sites of Herpes Simplex Virus Type 1 Isolates from Encephalitic, Facial and Genital Lesions and Ganglia

Abstract: SUMMARYThe distribution of restriction endonuclease (RE) sites was compared for 84 herpes simplex virus type 1 (HSV-1) isolates obtained from the ganglia, facial lesions, genital lesions and from brain tissue from herpes encephalitis cases. The isolates came from Canada, the U.K., the U.S.A. and Japan. Out of a total of 224 sites identified, 87 were variable. Three of the 30 most variable sites were at significantly (P < 0-05) different frequencies in groups of isolates from distinct anatomical sites of isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1

Year Published

1987
1987
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 52 publications
0
8
1
Order By: Relevance
“…Since gains or losses of cleavage sites are more efficient markers than fragment length (Roizman, 1979;Chaney et al, 1983b;Sakaoka et al, 1985Sakaoka et al, , 1986, they were chosen for the comparative analysis of isolates. In addition, the cleavage sites have been shown not to vary in epidemiologically related isolates (Lonsdale et al, 1979(Lonsdale et al, , 1980Roizman & Tognon, 1983;Maitland et al, 1983;Sakaoka et al, 1984Sakaoka et al, , 1986b or in randomly cloned stocks of a single strain (Lonsdale et al, 1980;Davison & Wilkie, 1981;Roizman & Tognon, 1983).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since gains or losses of cleavage sites are more efficient markers than fragment length (Roizman, 1979;Chaney et al, 1983b;Sakaoka et al, 1985Sakaoka et al, , 1986, they were chosen for the comparative analysis of isolates. In addition, the cleavage sites have been shown not to vary in epidemiologically related isolates (Lonsdale et al, 1979(Lonsdale et al, , 1980Roizman & Tognon, 1983;Maitland et al, 1983;Sakaoka et al, 1984Sakaoka et al, , 1986b or in randomly cloned stocks of a single strain (Lonsdale et al, 1980;Davison & Wilkie, 1981;Roizman & Tognon, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…Using a similar approach, Chaney et al (1983b) reported that HSV-1 strains from five different geographical locations could be significantly distinguished by the frequencies of RE sites. However, the number of isolates in this comparison was too small for definite conclusions to be drawn.…”
Section: Discussionmentioning
confidence: 99%
“…In order to compare the correlation coefficient (r) of every pair of RE sites. Pearson's product moment correlation coefficient was calculated with a 2 x 2 contingency table by using the same formula as that employed by Chaney et al (1983b). Nucleotide diversity.…”
Section: H Sakaoka and Othersmentioning
confidence: 99%
“…HSV-1 strains differ slightly in their DNA sequences, which are used as molecular markers of genomic polymorphism. The method generally used to differentiate HSV-1 strains is restriction fragment length polymorphism (RFLP) analysis of total HSV-1 DNA (4,7,26,36) or RFLP-PCR-based analysis (23,49,53). Determination of the nucleotide sequences of PCR-amplified DNA fragments encompassing reiterated regions (33) is another approach currently used to characterize the genomes of HSV-1 strains.…”
mentioning
confidence: 99%